Light quality regulates expression of chloroplast genes and assembly of photosynthetic membrane complexes - Glick, Richard E. (1986)
The concentrations of photosystem I (PSI) and photosystem II (PSII) reaction centers and the level of chloroplast reaction center gene transcripts were determined in pea plants grown under different light-quality regimes. In plants grown in light primarily absorbed by PSI (“red” light), the PSII/PSI reaction center ratio was 2-fold greater than that in plants grown in PSII-sensitizing (“yellow”) light. In addition, the ratio of a PSII gene (psbB) transcript to a PSI gene (psaA) transcript was 2.6 times greater in red-grown plants relative to yellow-grown plants. Thus, a differential reaction-center concentration in the thylakoid membrane was accompanied by a differential expression of reaction center genes, suggesting that the synthesis of chloroplast membrane complexes and the assembly of photosystems are regulated by light quality at the transcriptional and/or post-transcriptional level.